Instrumentation and sensors for the food industry - Kress-Rogers, Erika; Brimelow, Christopher J. B. (Woodhead Publishing in food science and technology., 2001)
The first edition of this book quickly established itself as the standard reference in its field, and the second edition consolidates this reputation. Keeping up with the rapid change in this area, there are 16 new contributors and 8 completely new chapters, as well as major revisions to existing chapters, making this second edition a substantially longer book.